The Role of Game Involvement on Attention to Ads: Exploring Influencing Factors of Visual Attention to Game Ads on Instagram Stories - Yi-Ting Huang; An-Di Gong (Human Behavior and Emerging Technologies)
Instagram Stories advertising has the advantages of precise targeting, diverse advertising formats, and a wide range of users; it has, thus, become an important medium for mobile game marketing. To find the most effective ad designs for mobile games on Instagram Stories, this study applied the stimulus-organism-response (S-O-R) theory to investigate how game involvement and ad designs affect users’ visual attention. Visual attention is an important physiological indicator of advertising effectiveness, and eye-tracking technology can accurately assess consumers’ visual attention. This study applied eye-tracking technology to 80 participants, grouped as follows: high-involvement gamers, low-involvement gamers, and nongamers. This study used the eye movement indicators for first fixation duration (FFD) and total fixation duration (TFD) to, respectively, evaluate the attentional salience and hold of mobile game ads. The ads were presented in three formats (5 s video, 15 s video, and 5 s image) with two types of content (gameplay and game characters). Results showed that the mobile game ads on Stories exerted the highest attentional hold on high-involvement gamers. In terms of ad format, video ads offered a higher attentional hold and attentional salience. In terms of ad content, ads that introduced game characters resulted in better attentional salience; however, ads that introduced gameplay exerted better attentional hold for nongamers. This study examined both individual differences in media users and ad design to provide recommendations for the personalization of mobile game ads for social media. For example, ads designed for a high-involvement gamer should incorporate more diverse and complex information. In addition, we found that when the marketing goal is the promotion of game characters, image ads are the most appropriate format.